The Causal Effect of Deficiency at English on Female Immigrants Labour Market Outcomes in the UK - Alfonso Miranda; Yu Zhu (University of Kent, School of Economics, 2013)
Using the first wave of the UK Household Longitudinal Survey, we investigate the extent to which deficiency at English as measured by English as Additional Language (EAL), contribute to the immigrant-native wage gap for female employees in the UK, after controlling for age, region of residence, educational attainment and ethnicity. We allow for endogeneity of EAL and correct for bias arising from self-selection into employment using a 3-step estimation procedure. We find very strong evidence of negative selection of EAL into employment. Moreover, we also present evidence of self-selection bias on the wage equation, which if uncorrected, would result in significant underestimation of the causal effect of EAL on the immigrant-native wage gap for women.
Keywords: J15; J31; J61; 330; English as Additional Language (EAL); immigrant-native wage gap; selectivity bias